2020
DOI: 10.1002/alz.12211
|View full text |Cite
|
Sign up to set email alerts
|

Long genes are more frequently affected by somatic mutations and show reduced expression in Alzheimer's disease: Implications for disease etiology

Abstract: Aging, the greatest risk factor for Alzheimer's disease (AD), may lead to the accumulation of somatic mutations in neurons. We investigated whether somatic mutations, specifically in longer genes, are implicated in AD etiology. First, we modeled the theoretical likelihood of genes being affected by aging‐induced somatic mutations, dependent on their length. We then tested this model and found that long genes are indeed more affected by somatic mutations and that their expression is more frequently reduced in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…We show that approximately 40% of all elongating RNAPII complexes are stalled by DNA damage in WT aged livers; thus, the identical aging signal that causes progeroid syndromes also occurs in normal aging. Interestingly, brains from patients with Alzheimer’s disease also displayed reduced expression of long genes compared to age-matched controls 60 , suggesting that the magnitude of transcriptional stress is involved in age-related disease etiology. Conversely, longevity-promoting intervention dietary restriction restores the loss of long gene expression 29 , indicating that longevity interventions can alleviate transcriptional stress.…”
Section: Discussionmentioning
confidence: 99%
“…We show that approximately 40% of all elongating RNAPII complexes are stalled by DNA damage in WT aged livers; thus, the identical aging signal that causes progeroid syndromes also occurs in normal aging. Interestingly, brains from patients with Alzheimer’s disease also displayed reduced expression of long genes compared to age-matched controls 60 , suggesting that the magnitude of transcriptional stress is involved in age-related disease etiology. Conversely, longevity-promoting intervention dietary restriction restores the loss of long gene expression 29 , indicating that longevity interventions can alleviate transcriptional stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, analysis of gene-length-dependent transcriptional changes reflect a promising indirect readout for measuring transcription stress and the effect of DR in Ercc1 Δ/− nervous system. Importantly, a bias of reduced expression of long genes also has been found in aged human nervous system ( Vermeij et al, 2016a ; Niedernhofer et al, 2018 ; Soheili-Nezhad et al, 2021 ), indicating that DNA-damage-induced transcription stress is an important factor contributing to nervous system aging and targeted by DR ( Vermeij et al, 2016a ). Future studies employing high resolution spatial transcriptomic approaches ( Asp et al, 2020 ; Lewis et al, 2021 ) may uncover the relationships between transcriptional abnormalities and neuronal degeneration in aging and progeroid models.…”
Section: Discussionmentioning
confidence: 99%
“…A second set of enriched pathways consisted of DNA damage pathways, including "UVB/C-induced MAPK signaling", "ATM signaling", and "p53 signaling". Recently, we have shown that several synaptic pathways are impaired in the hippocampus of AD patients by analyzing transcriptomic data and have also linked these findings to somatic DNA damage (Soheili-Nezhad et al, 2021). In this respect, an impaired p53-mediated DNA damage response has been observed in AD patient brains (Farmer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%